(untitled) (Research, Society and Development, 2025)
Introduction: Hantavirus is a zoonosis with worldwide distribution that represents a challenge to public health, especially in the southern region of Brazil, where there are the largest number of reported cases. It uses wild rodents as vectors, such as rats, mice, and mice. Objective: To analyze the epidemiological profile of Hantavirus cases in the southern region of Brazil. Methodology: This is an epidemiological, ecological, descriptive study with a quantitative approach, carried out by collecting data from secondary databases of the Department of Information Technology of the Unified Health System (DATASUS), from 2012 to 2022. The following variables were considered: race, sex, age group, infection environment, confirmation criteria, and evolution. Results and discussion: During the studied period, 788 cases of Hantavirus occurred in Brazil. The southern region was the most affected, with 345 cases (43.78%). The state of Santa Catarina (SC) was the most affected, accounting for a total of 165 infected people (47.82%). In the race variable, the most affected population was white, with the number of infected people being 300. Laboratory tests make diagnosis feasible. Conclusion: The study highlights the significant implications of hantavirus infection for the health of the population in Brazil, especially in the South region, where the disease is most prevalent. Therefore, in order to combat the disease, it is of fundamental importance to implement strategies that prevent humans from coming into contact with the waste excreted by infected rodents.